2016
DOI: 10.1017/s1092852916000250
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis of epilepsy: a multifaceted neuropsychiatric disorder

Abstract: Psychosis of epilepsy (POE) is a term applied to a group of psychotic disorders with a distinct phenomenology in which potential etiopathogenic mechanisms are believed to be closely related to a seizure disorder. POE can present as interictal psychotic episodes, which may often differ semiologically from primary schizophrenic disorder. They may present as ictal or postictal psychotic episodes and may be the expression of an iatrogenic process to pharmacologic and/or surgical interventions.Epilepsy and POE have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
43
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 93 publications
(162 reference statements)
0
43
1
Order By: Relevance
“…The bidirectional association between epilepsy and psychosis has been widely studied during the past century . Much of the evidence in this regard has emerged from experimental studies of kindling and electroconvulsive seizures, as well as the observed therapeutic effect of electroconvulsive therapy in psychotic and depressive disorders in humans …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bidirectional association between epilepsy and psychosis has been widely studied during the past century . Much of the evidence in this regard has emerged from experimental studies of kindling and electroconvulsive seizures, as well as the observed therapeutic effect of electroconvulsive therapy in psychotic and depressive disorders in humans …”
Section: Introductionmentioning
confidence: 99%
“…1 Much of the evidence in this regard has emerged from experimental studies of kindling and electroconvulsive seizures, 2 as well as the observed therapeutic effect of electroconvulsive therapy in psychotic and depressive disorders in humans. 3 The occurrence of psychosis and epilepsy is not coincidental. The annual incidence of schizophreniform psychosis in epilepsy (0.4%) is twice as high as that of schizophrenia in the general population (0.2%).…”
Section: Introductionmentioning
confidence: 99%
“…First, these patients typically receive antipsychotic medications to alleviate the comorbid “positive” (eg, delusions, hallucinations) and “negative” (eg, apathy, blunted affect) symptoms of schizophrenia. Antipsychotic medications, however, may not always be effective and may even exacerbate seizure frequency and severity . Second, due to the nature of their psychiatric comorbidities, these patients often fail to comply with prescribed anti‐epileptic medication regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Antipsychotic medications, however, may not always be effective and may even exacerbate seizure frequency and severity. 10 Second, due to the nature of their psychiatric comorbidities, these patients often fail to comply with prescribed anti-epileptic medication regimens. This lack of compliance also applies to other therapeutic interventions offered, including neurophysiologic (eg, EEG, MEG, MRI) assessments required for seizure monitoring or surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostically, there is a possibility that the seizure disorder could be presenting as mental illness such as in the psychoses of epilepsy (Kanner & Rivas-Grajales, 2016). Conversely, seizures could be mistaken as evidence of psychiatric illness (Mirsattari et al 2011).…”
mentioning
confidence: 99%